A Study on Customer Satisfaction of AirAsia Berhad - Teoh, Kok Ban; Gan, Kia Hui; Darishini, Letchumunen; Umamageswari, Umamageswari; Neoh, Kah Yong; Jivega, Nadarajah; Low, Yen Ling; Lu, Shuang; Mah, Ehy Tarh; Ma, Yan Qi (AIBPM Publisher, 2023)
This study explores customer satisfaction in the context of AirAsia Berhad, a prominent low-cost airline. It focuses on three key dimensions: tangible, assurance, and responsiveness. The research reveals that tangible factors, such as the physical aspects of service, significantly influence customer satisfaction. Assurance, which encompasses competence, courtesy, and reliability, also plays a crucial role in keeping customers content. Moreover, responsiveness, or the airline's ability to deliver prompt and efficient service, enhances overall satisfaction. Understanding these dimensions is vital for AirAsia and similar airlines, as addressing them can meet customer expectations, foster loyalty, and improve overall performance. This research offers insights into the complex relationship between service quality and customer satisfaction in the airline industry, guiding strategies for enhancing the passenger experience.